Effects of Alkali Swelling and Beating Treatments on Properties of Kraft Pulp Fibers - Kyoung-Hwa Choi; Ah Ram Kim; Byoung-Uk Cho (BioResources, 2016)
Three alkali swelling methods were used to treat two kinds of kraft pulp fibers. The morphological and chemical properties of the treated fibers were elucidated in terms of alkali concentration, with the aim of developing bulky paper and conserving wood resources. The effects of beating before and after alkali swelling were examined. The water retention value of fibers increased when higher concentrations of NaOH were used for swelling. Alkali swelling increased fiber width, while fiber length decreased. With increasing NaOH concentration, fibers became curled or kinked; the crystalline structure changed from cellulose I to cellulose II, and the crystalline index decreased. Beating before and after the alkali swelling affected the swelling behavior of kraft pulps, but there was no distinct influence on the crystalline structure. The beating treatment before alkali swelling improved the alkali swelling of fiber. However, beating after the alkali treatment diminished the alkali swelling effects. In addition, the beating after alkali swelling straightened the curled fibers.